Towards a Conscious Digital Generation: Efforts to Increase Knowledge and Attitudes about Cybersex among Adolescents - Dien Gusta Anggraini Nursal; Siti Nur Hasanah; Gebby Afrila; Mutia Mutia; Sabillah Nasitoh; Muhammad Sakhi Baretta (Warta Pengabdian Andalas, 2024)
The increasing prevalence of cybersex behavior among adolescents presents a growing concern, with potential risks to their physical and mental health. The ease of access and low cost associated with this behavior contribute to its proliferation. Based on interviews with students from X High School in Pariaman, it was found that a significant portion of the student population accesses pornography on the internet when exposed to online advertisements and during casual browsing. The primary objective of this initiative is to nurture a generation of digitally aware youth by enhancing their knowledge and shaping healthier attitudes regarding cybersex. The location of the activities was SMA X Pariaman City. A combination of active and passive approaches was employed. Active methods involved delivering lectures with prepared materials and informative video presentations. Passively, students were provided with informational leaflets and banners placed strategically in the school environment. Pre-test and post-test questionnaires were administered to gauge the effectiveness of the materials and videos in influencing participants' knowledge and attitudes. Statistical analysis, including the Wilcoxon test and Gain Score, reveals a notable increase in expertise and confirms the effectiveness of the counseling efforts. In summary, this program effectively enhances knowledge and attitudes about cybersex among adolescents, marking a significant step in addressing this pressing issue.